Characteristics and outcomes of hospitalized patients with Isolated and systemic cardiac sarcoidosis: Analysis of the Nationwide readmissions database 2016–2021 - Raheel Ahmed; Nitish Behary Paray; Hiroyuki Sawatari; Syed Emir Irfan Wafa; Kamleshun Ramphul; Mushood Ahmed; Hritvik Jain; Saurabh Deshpande; Mohammed Khanji; Athol Umfrey Wells; Peter Collins; Selma Mohammed; et al. (International Journal of Cardiology: Heart & Vasculature)
Objective: To identify any differences in the characteristics and outcomes of patients with Isolated cardiac sarcoidosis (iCS) vs systemic cardiac sarcoidosis (sCS). Patients and methods: All inpatient encounters in the Nationwide Readmission Database from 2016 to 2021 were analyzed for the rates, predictors, costs and mortality during index and unplanned 90-days readmissions for iCS and sCS patients. Patients with ischemic heart disease were excluded. Results: 1,667 patients were identified (57.8 % male), of which, 1,013 (60.8 %) had iCS and 654 (39.2 %) had sCS. The median (IQR) age of iCS patients was slightly older [57.0 (49.0–66.0) vs 56.0 (48.0–64.0), p = 0.04]. On index admission, iCS patients had higher prevalence of ventricular tachycardia (36.9 % vs 28.8 %, p = 0.001) and catheter ablation (5.6 % vs 2.8 %, p = 0.006). The predictors for all-cause readmissions were Charlson Comorbidity Index (CCI) (HR 1.19, 95 % CI 1.01–1.40, p = 0.04), age (HR 0.98 (0.97–1.00), p = 0.01) and the use of anticoagulant therapy (HR 1.92, 95 % CI 1.35–2.72, p < 0.001). Patients with sCS were more likely to be readmitted with heart failure compared to iCS patients (SHR 3.78, 95 % CI 1.11–12.94, p = 0.03). During subsequent readmission, iCS and sCS patients had comparable rates of in-hospital mortality, median length of stay and healthcare-associated costs. No independent predictors of in-hospital mortality at readmission were ascertained. Conclusions: Isolated CS patients, when compared to systemic CS, had a greater prevalence of ventricular tachycardia and catheter ablation. They were less likely to be re-hospitalized with heart failure within 90-days. Age, higher CCI, and use of anticoagulant therapy were predictors for all-cause readmissions.